(untitled) (Географический вестник=Geographical bulletin, 2017)
Определяются место и роль эрозионных и аккумулятивных процессов в формировании ложа крупных равнинных водохранилищ. Представлены последние данные о темпах и закономерностях осадконакопления в искусственных водоемах. В особую группу процессов морфолитогенеза в их глубоководных частях выделены псевдорусловые процессы. CHANNEL PROCESSES AND MORPHOLITOGENESIS IN BOTTOM OF RESERVOIRS Geomorphological researches at the Kama reservoirs have revealed the fact that the fluvial (erosion and accumulation) processes play an important role in the bulge transformation of the pond floors. The channel processes are being spread far, beyond the bounds of the fluctuating backwater zone and influence on the rate and character of morpholitogenesis in the medium and lower reservoirs’ parts actively. The channel flows act using the old channels of rivers. The important constituent of morpholitogenesis of the deepest part of ponds’ beds is the complex of pseudo-channel processes, modelling the channel narrow in the correspondence with the peculiarities of hydrophysical, subsoil and some other pond processes. The reason of appearance of the processes turns out to be the channel itself.